Leading Remote Organizations Strategies for Managing Effective Knowledge Sharing Within Teams - McFadden, Jessica; McClain, William Lee (Journal of Leadership, Accountability and Ethics, 2024)
Remote teams have become an integral part of the operations of global organizations in an increasingly digital era. The complexities of knowledge sharing and management within teams were explored. A focus was placed on the leadership practices that influenced complexities. Using qualitative insights from participants, the importance of transformational leadership in fostering a culture of open communication, trust, and collaboration in remote settings was emphasized in the study. The findings indicated that hat leaders who showed transformational traits such as charisma, authenticity, intellectual stimulation, and individualized consideration enhanced knowledge-sharing within their teams. Leaders’ practices promoted knowledge sharing and positively impacted team productivity, job satisfaction, and retention. In remote work, transformational leadership was pivotal in ensuring effective knowledge management, underscoring its importance for contemporary organizations aiming for growth and innovation in a digital landscape.